2012
DOI: 10.4103/0253-7613.91880
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant activity of two important memory enhancing medicinal plants Baccopa monnieri and Centella asiatica

Abstract: Background:Free radicals or highly reactive oxygen species are capable of inducing oxidative damage to human body. Antioxidants are the compounds which terminate the attack of reactive species and reduce the risk of diseases. Both Baccopa monnieri and Centella asiatica are used in treatment of brain disorders in humans and have almost similar effects.Objective:The study was conducted to determine the antioxidant properties of two well-known memory enhancer medicinal plants Baccopa monnieri and Centella asiatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 8 publications
(9 reference statements)
1
43
0
1
Order By: Relevance
“…Plantaginaceae Leaves Perennial speech disorders (Chopra et al 2002), in premature ejaculation (Anuradha et al 1994), flatulence (Mohan and Singh 1996), abdominal pain (Chetty et al 1998), Aging, Antioxidant, Stress, cough, cold (Pareek 1994), (Malhotra and Moorthy 1973), (Singh and Aswal 1992), rheumatism (Singh 1993), (Bedi 1978) Antioxidant activity (Meena et al 2012), anti-inflammation ) (Mistry et al 2014) 14 Kolu…”
Section: Bacopa Monnierimentioning
confidence: 99%
“…Plantaginaceae Leaves Perennial speech disorders (Chopra et al 2002), in premature ejaculation (Anuradha et al 1994), flatulence (Mohan and Singh 1996), abdominal pain (Chetty et al 1998), Aging, Antioxidant, Stress, cough, cold (Pareek 1994), (Malhotra and Moorthy 1973), (Singh and Aswal 1992), rheumatism (Singh 1993), (Bedi 1978) Antioxidant activity (Meena et al 2012), anti-inflammation ) (Mistry et al 2014) 14 Kolu…”
Section: Bacopa Monnierimentioning
confidence: 99%
“…Under this perspective, several studies have demonstrated the beneficial effects of antioxidant activities of medicinal plants to control or treat diseases associated to redox stress and inflammation, such as type 2 diabetes mellitus, hypertension and degenerative pathologies (Aruoma 1998, Alves et al 2010, Krishnaiah et al 2011, Meena et al 2012). Thus, the search for new species that combine antioxidant properties and reduced side effects is recommended, as evaluated for the extraction and fractions isolated from M. hirsuta.…”
Section: Phytochemistry and Toxicity Of Mansoa Hirsuta 323mentioning
confidence: 99%
“…The herb is used in different purposes, such as a memory enhancer, immune booster, strength promoting, antiepileptic, antianxiety, and adaptogen. 28,29 The aqueous extracts of C. asiatica were evaluated in intracerebroventricular streptozotocin-induced cognitive impairment and oxidative stress in rats, and it was found that the plant possessed cognitive-enhancing effect and also an involvement of antioxidant mechanism. 30 The use of this plant is also found clinically for the anxiety neurosis and for mentally retarded children 23 as well and showed improvement in the short-term memory and learning abilities in both animal models and humans.…”
Section: Mandukparni (C Asiatica L Urb)mentioning
confidence: 99%
“…The plant also possesses anxiolytic properties which are associated due to binding to cholecystokinin receptors, which are G protein coupled-type receptors and bind the peptide hormones cholecystokinin or gastrin and were considered to play a significant role in modulation of anxiety, memory, and hunger and nociception in animals and humans. 29,32 The herb is also known to invigorate the nervous system and brain and increase concentration, attention span, and combat aging.…”
Section: Mandukparni (C Asiatica L Urb)mentioning
confidence: 99%